CTA Project Completion Report: AgriHack Talent: Focus on Pitch AgriHack - Lohento, Ken; Koutchade, Folake; Bellinzas, Giorgio (Technical Centre for Agricultural and Rural Cooperation, 2020)
CTA’s AgriHack Talent initiative aimed to strengthen youth-led digital innovation and entrepreneurship in agriculture in African, Caribbean and Pacific countries. It was a key part of CTA’s strategy to encourage youth’s meaningful involvement in agriculture and promote youth employment and agricultural transformation through innovations. Co-designed with young innovators and partners, the AgriHack Talent project included: • competitions to develop information and communication technology (ICT) applications for agriculture (hackathons) when there is a need • a start-up competition (called Pitch AgriHack) targeting young companies already offering e-agriculture services • capacity building, mentorship and incubation opportunities • promotional and networking opportunities • facilitation of access to grants and investments to scale-up services offered.